Michel Mangenot – Robert Polet: European Social Dialogue and the Civil Services: Europeanisation by the back door? (Czech Journal of International Relations, 2005)
Michel Mangenot – Robert Polet: European Social Dialogueand the Civil Services: Europeanisation by the back door?1st ed. Maastricht: EIPA, 2004, 161 stran, ISBN 90-6779-195-4.